Perencanaan Perawatan Motor Penggerak Wesel Type T84M dengan Menggunakan Metode RCM (Reliability Centered Maintenance) di Daop 2 Bandung - Arief Darmawan; Dimas Adi Perwira; Edi Nyoto Setyo Marsusiadi; Else Frida Sukresnawati; Arum Putri Maharani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Daop 2 Bandung is one of the train operational areas where each station has a signaling system to maintain safety and regulate train operations so that they remain effective and efficient. This research aims to determine the maintenance planning system for the Type T84M Wesel Drive Motor using the RCM (Reliability Centered Maintenance) method in Daop 2 Bandung. The method used is RCM (Reliability Centered Maintenance) which focuses on secondary data in the form of historical data on disturbances on the T84M draft motorbike which is used to calculate maintenance time intervals based on the results of data distribution for each component according to the RCM (Reliability Centered Maintenance) method. The research results show that the appropriate maintenance tasks for wesel motor components are scheduled disposal tasks and scheduled restoration tasks. The T84M draft motorbike has a reliability value of 43.2% and an availability value of 99% and the recommended maintenance interval for the T84M draft motorbike is 3 days.